70 GSa/s and 51 GHz bandwidth track‐and‐hold amplifier in InP DHBT process. Issue 6 (1st March 2013) - Deza, J.; Ouslimani, A.; Konczykowska, A.; Kasbari, A.; Godin, J.; Pailler, G.
Abstract : A differential 70 GSa/s track‐and‐hold amplifier has been designed and fabricated in a 320 GHz‐fT InP double heterojunction bipolar transistor process. Measurements show a 51 GHz small‐signal bandwidth with an S 11 parameter lower than −15 dB up to 56 GHz. The transient operation is verified up to 70 GSa/s. 60 GSa/s spectral measurements give total harmonic distortion <−46 dB up to 7 GHz and <−37 dB over the whole measurement range.